The Significance Risk for Factors of Labour, Material, and Equipment on Construction Project Quality - Saiful Husin; Mubarak Mubarak; Fachrurrazi Fachrurrazi (Aceh International Journal of Science and Technology, 2019)
The construction involves a series of activities that possibly face problems or risks. The risk probability is an uncertain condition that results in a negative impact on the project objectives. Threats can come from the resources factor in a construction project, such as labour, materials, and equipment. The handling of risks in construction work needs to be further reviewed. It is to find risk factors and risk variables contributing to high risk to achieve the quality objectives of construction implementation. The purpose of this study was to analyze the most significant risk towards the quality of construction associated with the condition of the Province of Aceh during 2000-2015. The situation is classified in three periods, namely political conflict (2000-2004 as Period I), rehabilitation and reconstruction (2005-2009 as Period II), and post-rehabilitation and reconstruction (2010-2015 as Period III). Dataset is collected using questionnaires to 15 large qualified contractor companies to capture construction quality information. The risk significance identified based on Risk Importance Index (RII) for frequency and severity of factors and variables. There are 7 variables for labour resources, 10 variables for material resources, and 17 variables for equipment resources. The quality of construction mostly affected by the labour resources factors in Period I and Period III. The risk comes from the variable discipline of workers who are not good (A3). For Period II, the lack of labour capacity (A2) variable become as the most significant risk.